Experimental validation of theoretically predicted cut-off of L1–L3M4, 5 transitions at Z= 50 through measurements of fluorescence and Coster–Kronig yields for Sn and Sb. (1st April 2021) - Kaur, Sandeep; Ayri, Vibha; Kumar, Anil; Czyzycki, M; Karydas, A G; Puri, Sanjiv
Abstract: In the present work, we have deduced the fluorescence ( ω 1, ω 2, ω 3 ) and Coster–Kronig (CK)( f 12, f 13, f 23 ) yields for Sn ( Z = 50) and Sb ( Z = 51) from the L i ( i = 1–3) sub-shell x-ray intensities measured using the energy tunable synchrotron radiation employing the selective photoionization method. For both the elements, yields have been obtained using two sets of theoretical photoionization cross sections based on the non-relativistic Hartree–Fock–Slater (HFS) model and the self-consistent Dirac–Hartree–Fock (DHF) model. In case of Sb, we have obtained a third set of measured yields also by using the experimental photoionization cross sections evaluated from independent measurements of the mass-attenuation coefficients. The experimental yields for Sb are reported for the first time by us. We have compared the present deduced fluorescence and CK yields with the Dirac–Hartree–Slater model based values, the semi-empirical values tabulated by Krause and the earlier reported values. In case of Sn, using the DHF and the HFS model based photoionization cross sections, two sets of present measured L1 sub-shell fluorescence yields ( ω 1 ) are found to be 0.039 ± 0.007 and 0.036 ± 0.003, and the CK yields ( f 13 ) are found to be 0.428 ± 0.107 and 0.405 ± 0.028, respectively. In case of Sb, using three sets of the photoionization cross sections (DHF, HFS and recent experimental values), the ω 1 values are measured to be 0.042 ± 0.007, 0.040 ± 0.004 and 0.047 ± 0.005, and the CK yields are measured to be 0.343 ± 0.085, 0.297 ± 0.021 and 0.247 ± 0.022, respectively. The comparison of these present measured yields with the theoretical values provided a reliable experimental evidence indicating cut-off of the intense L1 –L3 M4, 5 CK transitions at Z = 50.